ANALISIS KARAKTERISTIK SOAL KEMAMPUAN KONEKSI MATEMATIKA PENSKORAN POLITIMUS - Rosid Bahar; Heri Retnawati (JURNAL TARBIYAH, 2022)
The objectives of this study were 1) to determine the fit of the model on the polytomic scoring, and 2) to determine the quality of the mathematical connection instrument. This study uses a quantitative approach with exploratory descriptive research. The research subjects were the responses of the students of class VIII MTs Fadris Tasikmalaya Regency with a total of 135 participants. The data collection technique used an instrument of mathematical connection ability with a total of 5 description questions with a polytomus score. The data analysis used the Generalized Artificial Credit Model (GPCM) approach with the help of the R Studio software program with the irtGUI package. Based on the results of the analysis, this instrument has met the IRT assumption test, namely unidimensionality and local independence. Analysis with the R studio program also resulted in a model fit with the GPCM approach. The results of the analysis using the GPCM approach show that 3 of the 5 description questions presented have a quality that is suitable for use, because they meet the validity and reliability standards based on item fit and item information functions.